Efektifitas Pembelajaran Di Kelas 1 Madrasah Ibtidaiyah: Integrasi Animasi Stop Motion dan Pembelajaran Berbasis Masalah (PBL) Sebagai Inovasi Pendidikan yang Efektif - Rohmah, Miftahul; Rasimin (Indonesian Journal of Humanities and Social Sciences, 2023)
This article aims to examine learning media innovation by utilizing stop motion animation integrated with the Problem-Based Learning (PBL) learning model to be applied in the context of grade 1 of Madrasah Ibtidaiyah. The research method applied is Research and Development (R & D). The research subjects involved low grade teachers in Central Java, and the product trial subjects were grade 1 students of MI Muhammadiyah PK Blimbing Gatak Sukoharjo. The results of the study revealed that, although PBL is considered indispensable at the low-grade level, its implementation becomes difficult at grade 1. In contrast, stop motion animation media proved to be very suitable for low-grade students, especially at the grade 1 level. The trial process of this innovative product showed that the integration of stop motion animation with PBL was feasible and effective in improving learning outcomes of grade 1 students. The implications of this study can provide practical guidance for grade 1 teachers in facing the challenges of PBL and offer innovative solutions through the use of stop motion animation media.